2016
DOI: 10.1210/jc.2015-3543
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain and Dyslipidemia in Early Adulthood Associate With Polycystic Ovary Syndrome: Prospective Cohort Study

Abstract: Symptoms or diagnosis of PCOS are associated with dyslipidemia, hyperandrogenemia, and significantly increased weight gain, especially in early adulthood. This observation is important because it may identify a sensitive time period when weight gain plays a crucial role in the emergence of PCOS and when preventive actions against metabolic and cardiovascular diseases should be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
119
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 40 publications
10
119
1
Order By: Relevance
“…Our previous study reported that weight gain, especially in early adulthood, associated with later diagnosis of PCOS (Ollila et al, 2016). In addition, previous studies have also been inconsistent about whether PCOS per se presents as an independent risk factor for developing T2DM (Legro et al, 1999), whether there is a synergistic effect between PCOS and BMI (Boudreaux et al, 2006;Joham et al, 2014) or whether the association between PCOS and T2DM is entirely attributable to obesity (Gambineri et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Our previous study reported that weight gain, especially in early adulthood, associated with later diagnosis of PCOS (Ollila et al, 2016). In addition, previous studies have also been inconsistent about whether PCOS per se presents as an independent risk factor for developing T2DM (Legro et al, 1999), whether there is a synergistic effect between PCOS and BMI (Boudreaux et al, 2006;Joham et al, 2014) or whether the association between PCOS and T2DM is entirely attributable to obesity (Gambineri et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Our finding suggests that TT/DHT ratio may speak for metabolic disturbance, not only in PCOS but also in "theoretically" healthy subjects without clinical and hormo- [11]. Subsequently, a number of studies were conducted in order to identify potential predictors of the metabolic risk in this group of patients.…”
Section: Discussionmentioning
confidence: 87%
“…When the measurement was missing, the self-reported values were used. No statistical difference was observed between the measured and the self-reported BMIs (17). …”
Section: Methodsmentioning
confidence: 87%
“…At ages 31 and 46, sex serum T (17) and sex hormone-binding globulin (SHBG) (15) were assayed as previously described. Briefly, T was assayed using Agilent triple quadrupole 6410 liquid chromatography/mass spectrometry equipment with an electrospray ionization source operating in positive-ion mode (Agilent Technologies, Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%